Anatomical variations in the Circle of Willis and the formation and rupture of intracranial aneurysms: A systematic review and meta-analysis - Feng, Lu; Mao, He-Jiao; Zhang, Ding-Ding; Zhu, Yi-Cheng; Han, Fei (Frontiers in Neurology, 2023)
Background The anterior (AcomA) and posterior communicating arteries (PcomA) are two of the most frequent sites for intracranial aneurysms. Anatomical variations in the Circle of Willis (COW) are frequently observed in patients with AcomA and PcomA aneurysms. Strong evidence is needed to determine the pooled estimate of the effect of COW variations on the formation and rupture of these aneurysms. Aim This systematic review and meta-analysis aimed to establish the effect of COW variations on the formation and rupture of AcomA and PcomA aneurysms using available studies. Summary of review PubMed, Embase, and Web of Science databases were systematically searched for studies published in English before September 21, 2022. Studies investigating AcomA aneurysms and the hypoplastic/aplastic A1 segment of the anterior cerebral artery and PcomA aneurysms and hypoplastic/aplastic PcomA or fetal-type posterior cerebral artery (FTP) were included. The heterogeneity of the studies was assessed using Cochran Q-test and I2 statistic. Pooled estimate was assessed using either a random- or fixed-effects model based on the heterogeneity of the studies. Among the 4,932 studies, 21 were eligible and included in the analysis. The presence of hypoplastic/aplastic A1 was significantly correlated with the formation [OR (95% confidence interval [CI]) = 7.97 (5.58, 11.39), P < 0.001] and rupture [OR (95%CI) = 1.87 (1.29, 2.72), P < 0.001] of AcomA aneurysms. Significant associations between FTP and both the formation [OR (95%CI) = 2.15 (1.41, 3.30), P < 0.001] and rupture [OR (95%CI) = 1.72 (1.26, 2.36), P < 0.001] of PcomA aneurysms were observed. Conclusions Significant associations were observed between COW variations and both the formation and rupture of AcomA and PcomA aneurysms. This can help in determining interventions for patients with aneurysms. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=225149, identifier: CRD42021225149.